Från enspråkig till tvåspråkig ordbok - Martola, Nina (Nordiske Studier i Leksikografi, 1995)
Compiling a bilingual dictionary on the basis of a monolingual one means enormous advantages. There are, however, also problems attaching to it. When the languages involved are two as structurally different languages as Finnish and Swedish, there are probably more problems than if the languages are structurally close to each other. This article desclibes some ofthe problems we have had on the macrostructural level duling our work on a new !arge Finnish-Swedish dictionary.